How Education Policy Shapes Literacy Instruction Understanding the Persistent Problems of Policy and Practice - Gabriel, Rachael (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Reading instruction is the most legislated area of education and the most frequently referenced metric for measuring educational progress. This book traces the trajectories of policy issues with direct implications for literacy teaching, learning, and research in order to illustrate the dynamic relationships between policy, research, and practice as they relate to perennial issues such as: retention in grade, remediation, intervention, instruction for English learners, early literacy instruction, coaching, and leadership. Using policy documents and peer-reviewed articles published from the 1960s to the present, the editor and authors illustrate how issues were framed, what was at stake, and how policy solutions to persistent questions have been understood over time. In doing so, the book link a generation of scholars with research that illustrates trajectories of development for ideas, strategies, and solutions. Rachael Gabriel is Professor of Literacy Education at the University of Connecticut, USA. She studies the intersections of education policy and classroom practice, prepares literacy specialists and doctoral students, and supports teachers and schools to build systems that create equitable opportunities to develop literacy.
1. Introduction -- 2. Retention in Grade and 3rd Grade "Trigger" Laws: History, Pitfalls and Politics -- 3. Remedial Programs: Identification, Instruction and Impacts of a Separate System for Learning -- 4. Early Reading Instruction: Politics and Myths about Materials and Methods -- 5. Cumulative Disadvantage: Differential Experiences of Students with Reading Difficulties -- 6. A Language for Literacy Learning: Language Policy, English Learners and Literacy Instruction -- 7. How Literacy Policy Shapes Teacher Quality: Coaching, Evaluation and Measures of Teacher Knowledge -- 8. Conclusion. .
Keywords: Education and state; Literacy; Language and languages-Study and teaching; Education-Curricula.; Teaching; Inclusive education; Educational Policy and Politics; Literacy; Language Education; Curriculum Studies; Didactics and Teaching Methodology; Inclusive Education